2022
DOI: 10.3390/en15093254
|View full text |Cite
|
Sign up to set email alerts
|

The Errors of Electronic Energy Meters That Measure Energy Consumed by LED Lighting

Abstract: Various metrological aspects for the correct measurements of electrical energy that is consumed by energy-saving (mainly LED) single phase loads are discussed in this paper. One of the most important problems presented here concerns the question of how strong distortions of the current waveform, introduced by typical LED lighting, affects the operation of electronic energy meters. Measurement results for the energy consumption of different LED lamps used in households in various conditions, alongside comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In particular, in [4] a significant influence of the parameters of measuring transformers on the metering unit operation accuracy was determined, especially when the power factor of load changes. It was also experimentally found that the accuracy of electricity metering is reduced due to the non-sinusoidal nature of load [5], especially in the case of LED lighting [6]. A priori uncertainty estimates may significantly exceed actual values.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In particular, in [4] a significant influence of the parameters of measuring transformers on the metering unit operation accuracy was determined, especially when the power factor of load changes. It was also experimentally found that the accuracy of electricity metering is reduced due to the non-sinusoidal nature of load [5], especially in the case of LED lighting [6]. A priori uncertainty estimates may significantly exceed actual values.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…An https://www.indjst.org/ automatic electricity bill generating system and proper monitoring of each appliance is the need of the hour. Though various technologies/approaches have been developed to measure the power consumption more smartly compared to conventional meters (Electro-Mechanical Induction Type), which include, Electronic Energy Meters (1) and Internet of Things (IoT)-based Smart Energy Meters (2) , the proposed smart energy meters have been suffered in several aspects in one or other way.…”
Section: Introductionmentioning
confidence: 99%